The Integration of Ahmad Dahlan’s Teachings Through Psychoeducation-Based Virtual Reality to Enhance Students’ Peace - Salsa Puspita Dwi Djajuli; Wahyu Nanda Eka Saputra; Hardi Santosa; Irvan Budhi Handaka; Rohmatus Naini; Salsa Puspita Dwi Djajuli; Wahyu Nanda Eka Saputra; Hardi Santosa; Irvan Budhi Handaka (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2027)
This study aims to test the effectiveness of virtual reality (VR)-based psychoeducation based on the teachings of K.H. Ahmad Dahlan in improving the calmness of vocational high school students. The study used a quantitative approach with a quasi-experimental method through a non-equivalent control group pretest-posttest design. The study participants consisted of 16 11th-grade students identified as having low levels of comfort and were divided into an experimental group and a control group. The experimental group received five sessions of VR-assisted psychoeducation that integrated the spiritual-humanistic values of K.H. Ahmad Dahlan, while the control group received treatment as usual. Data were collected using a validated Peace Scale consisting of 26 items covering aspects of self-harmony, social harmony, and environmental harmony. The instrument demonstrated good reliability with a Cronbach's Alpha coefficient of 0.849. Data analysis was performed using the Mann–Whitney U test to test for differences between groups. The results showed a significant increase in calmness in the experimental group, with the average score increasing from 70.0 to 81.6, while the control group only increased from 70.0 to 73.0. Statistical analysis showed a significant difference between the two groups (p < 0.05). These findings indicate that VR-based psychoeducation integrated with the spiritual-humanistic values of K.H. Ahmad Dahlan is effective in increasing students' calmness and has the potential to be an innovation in guidance and counseling services. However, this study has limitations in the relatively small sample size and short duration of the intervention.